Accelerated Production of Biopharmaceuticals via Microwave-Assisted Freeze-Drying (MFD) - Nicole Härdter; Raimund Geidobler; Ingo Presser; Gerhard Winter (MDPI AG, 2023)
Recently, attention has been drawn to microwave-assisted freeze-drying (MFD), as it drastically reduces the typically long drying times of biopharmaceuticals in conventional freeze-drying (CFD). Nevertheless, previously described prototype machines lack important attributes such as in-chamber freezing and stoppering, not allowing for the performance of representative vial freeze-drying processes. In this study, we present a new technical MFD setup, designed with GMP processes in mind. It is based on a standard lyophilizer equipped with flat semiconductor microwave modules. The idea was to enable the retrofitting of standard freeze-dryers with a microwave option, which would reduce the hurdles of implementation. We aimed to collect process data with respect to the speed, settings, and controllability of the MFD processes. Moreover, we studied the performance of six monoclonal antibody (mAb) formulations in terms of quality after drying and stability after storage for 6 months. We found drying processes to be drastically shortened and well controllable and observed no signs of plasma discharge. The characterization of the lyophilizates revealed an elegant cake appearance and remarkably good stability in the mAb after MFD. Furthermore, overall storage stability was good, even when residual moisture was increased due to high concentrations of glass-forming excipients. A direct comparison of stability data following MFD and CFD demonstrated similar stability profiles. We conclude that the new machine design is highly advantageous, enabling the fast-drying of excipient-dominated, low-concentrated mAb formulations in compliance with modern manufacturing technology.